ANALISIS POLA KONSUMSI RUMAH TANGGA TERHADAP TINGKAT KETAHANAN PANGAN DI DESA RIANGBAO, KABUPATEN LEMBATA, NUSA TENGGARA TIMUR - Khairiah, Khairiah; Sugianty, Ai Shanti; Sakina Yeti Kiptiyah (Nusantara Hasana Journal, 2025)
Food security is a condition of food fulfillment for households that includes availability, access, and utilization. This study aims to analyze the influence of household consumption patterns on the level of food security in Riangbao Village, Lembata Regency, East Nusa Tenggara. This study used a descriptive qualitative approach with the support of quantitative analysis through multiple linear regression. The sample consisted of 59 households selected using the slovin formula and purposive sampling technique. Data were collected through observation, interviews, and documentation (primary data), and supported by secondary data from BPS and the village. The results of the research on 59 households found that food security and food insecurity were found in small households (1-3 people), while food insufficiency and food insecurity were found in medium households (4-5 people) and large households (>6 people). The average level of energy consumption was highest in small, medium and large households. The consumption pattern of Riangbao Village community is still dominated by carbohydrate sources with limited food diversity. The regression results show that the variable expenditure on rice, fish, vegetables, fruit and oil has a significant effect on household food security. The variables of income and number of family members did not show a significant effect. This finding indicates that food security is determined more by the composition of food consumption than by economic factors.